2009
DOI: 10.1016/j.micpath.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Differential ability of periodontopathic bacteria to modulate invasion of human gingival epithelial cells by Porphyromonas gingivalis

Abstract: Periodontitis is a polymicrobial infection caused by selected gram-negative bacteria including Porphyromonas gingivalis. Host cell invasion by P. gingivalis has been proposed as a possible mechanism of pathogenesis in periodontitis. The aim of the present study was to assess the influence of periodontopathogens on P. gingivalis invasion of gingival epithelial cells in polymicrobial infection. P. gingivalis was tested for its ability to invade a human gingival epithelial cell line Ca9-22 in co-infection with pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 29 publications
4
49
1
Order By: Relevance
“…A study by Saito et al showed that F. nucleatum, a resident of the oral cavity, enhances the transportation of P. gingivalis inside epithelial cell monolayers in vitro. However, coincubation with another species, A. actinomycetemcomitans or T. forsythia, resulted in the abrogation of P. gingivalis invasion (184). The enhanced invasion of the epithelium may promote the further degradation of gum tissue and increase host inflammation.…”
Section: Considerations For Design and Use Of Polymicrobial Vaccinesmentioning
confidence: 99%
“…A study by Saito et al showed that F. nucleatum, a resident of the oral cavity, enhances the transportation of P. gingivalis inside epithelial cell monolayers in vitro. However, coincubation with another species, A. actinomycetemcomitans or T. forsythia, resulted in the abrogation of P. gingivalis invasion (184). The enhanced invasion of the epithelium may promote the further degradation of gum tissue and increase host inflammation.…”
Section: Considerations For Design and Use Of Polymicrobial Vaccinesmentioning
confidence: 99%
“…The previously accepted "red complex"-along with other cultivable bacteria species, such as Prevotella intermedia, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, Selenomonas noxia, and Eubacterium nodatum-is associated with periodontitis (Kolenbrander et al, 2002(Kolenbrander et al, , 2006Saito et al, 2009). In addition, organisms such as Selenomonas, Synergistes, Desulfobulbus, TM7 (new candidate bacterial division), and Filifactor alocis have been identified as potential pathogens in a number of independent studies (Dewhirst et al, 2010;Griffen et al, 2012).…”
Section: Yet-to-be-cultured Bacterial Communitiesmentioning
confidence: 99%
“…Historically, periodontal disease is associated with several pathogens contributing to a complex microbial milieu which can initiate or directly contribute to host tissue destruction (5). Bacteria such as Porphyromonas gingivalis, Prevotella intermedia, Aggregatibacter (Actinobacillus) actinomycetemcomitans, Tannerella forsythia, and Treponema denticola have previously been demonstrated to be major pathogens associated with periodontal diseases (6)(7)(8). A comparative oral microbiome analysis of the healthy and diseased states has indicated diversity in the microbial communities (9,10).…”
mentioning
confidence: 99%